Spectroscopy of hot γ Doradus and A–F hybrid Kepler candidates close to the hot border of the δ Scuti instability strip. Issue 3 (11th February 2020) - Kahraman Aliçavuş, F; Poretti, E; Catanzaro, G; Smalley, B; Niemczura, E; Rainer, M; Handler, G
ABSTRACT: If γ Dor-type pulsations are driven by the convective blocking mechanism, a convective envelope at a sufficient depth is essential. There are several hot γ Dor and hybrid star candidates in which there should not be an adequate convective envelope to excite the γ Dor-type oscillations. The existence of these hot objects needs an explanation. Therefore, we selected, observed, and studied 24 hot γ Dor and hybrid candidates to investigate their properties. The atmospheric parameters, chemical abundances, and v sin i values of the candidates were obtained using medium-resolution ( R = 46 000) spectra taken with the Fibre-fed Échelle Spectrograph instrument mounted at the Nordic Optical Telescope . We also carried out frequency analyses of the Kepler long- and short-cadence data to determine the exact pulsation contents. We found only five bona fide hot γ Dor and three bona fide hot hybrid stars in our sample. The other 16 stars were found to be normal γ Dor, δ Sct, or hybrid variables. No chemical peculiarity was detected in the spectra of the bona fide hot γ Dor and hybrid stars. We investigated the interplay between rotation and pulsational modes. We also found that the hot γ Dor stars have higher Gaia luminosities and larger radii compared to main-sequence A–F stars.